(untitled) (Global Journal of Science Frontier Research, 2018)
It is possible that as the dominate component of our cosmos, dark matter/dark energy, could be a driving force behind black hole(BH) formation at all scales in our universe. There is reason to believe that the extreme density of baryonic matter/gravity that produces stellar formation throughout our universe and its end of life transition explosion seen in supernova produces enough outward pressure it pulls in dark matter/dark energy (DM/DE) into the stellar core. This extreme event seen throughout our universe could conceivably produce enough negative pressure at its core to "suck-in" DM/DE from the other side of the baryonic matter/cosmic dark matter fractal field/interface(BM/CDMFF/I); creating a super massive injection of dark matter derived gravity within the collapsing star core fueling the extreme gravity conditions and the resulting implosion believed to occur in black hole (BH) formation of massive Chandra limit stars of all types. The Cosmic Dark Matter Fractal Field theory as described in the book "The Great Cosmic Sea of Reality" has given science a new paradigm to consider when examining our reality in a very different way.